Stainless steel plumbing. (NiDI, 1997)
The information in this booklet is tailored for designers, plumbers, end-users, maintenance engineers and others interested in providing reliable potable water systems. It covers: the nature of stainless steel; corrosion resistance; disinfection of stainless steel; tubing standards; fittings; fabrication and handling.
"December 1997."
Keywords: Plumbing -- Equipment and supplies.; Stainless steel.; elektronické knihy; electronic books